Question:

If \(a\) and \(b\) are two non-negative integers such that \(a + b = 5\), which of the following statements are then always true?

  1. \(a \ne b\)
  2. Either \(a > 2\) or \(b > 2\).

Provide a proof to support your claim.

Toggle answer

Answer:

Both statements are true.

First statement

If \(a = b\), then \(a + a = 2a = 5\), which means that \(a = 2.5\). This is impossible, since \(a\) was assumed to be an integer.

Second statement

By contradiction

Let's assume that \(a \le 2\) and \(b \le 2.\) But then \(a + b \le 4.\) So (by De Morgan’s laws) therefore either \(a > 2\) or \(b > 2\).

Logic proof

If it is not the case that \(a > 2\), then \(a\) must be strictly less than \(3\). So,

\(\lnot(a > 2) \equiv a < 3 \quad\) and \(\quad a < 3 \implies 5 - a > 5 - 3 = 2\).

Now, \(a + b = 5 \implies b = 5 - a\), so \(\lnot(a > 2) \implies b > 2\). And this is all we need, since \(\lnot P \implies Q\) is logically equivalent to \(P \vee Q\), as the following truth table shows.

\(P\) \(Q\) \(P \vee Q\) \(\lnot P\) \(\lnot P \implies Q\)
\(F\) \(F\) \(\bf{F}\) \(T\) \(\bf{F}\)
\(F\) \(T\) \(\bf{T}\) \(T\) \(\bf{T}\)
\(T\) \(F\) \(\bf{T}\) \(F\) \(\bf{T}\)
\(T\) \(T\) \(\bf{T}\) \(F\) \(\bf{T}\)

Exhaustion

Although not the most elegant of solutions, simply considering all possible values of \(a\) and \(b\) also serves as a direct proof of both statements. Since \(a\) and \(b\) are non-negative, \(0 \le a, b \le 5\).

\(a\) \(b\)
\(0\) \(\bf{5}\)
\(1\) \(\bf{4}\)
\(2\) \(\bf{3}\)
\(\bf{3}\) \(2\)
\(\bf{4}\) \(1\)
\(\bf{5}\) \(0\)

Generalized proof by induction

The statement can be seen as an instance of the more general form, $$ \forall a, b, z \in \mathbb{Z}_{\ge 0} : a + b = 2z + 1 \implies a > z \vee b > z, $$

with \(z = 2\). Since \(b = 2z + 1 - a\), we can instead phrase this as $$ a > z \vee 2z + 1 - a > z. $$

The proof will then proceed by induction. Let \(P(n)\) be the proposition that \(n > z\) or \(2z + 1 - n > z\). The base case \(P(0)\) holds, since \(2z + 1 - 0 > z\). It remains to show that \(\forall k \in \mathbb{Z}_{\ge 0} : P(k) \implies P(k + 1)\). So, assuming (by the induction hypothesis) that either \(k > z\) or \(2z + 1 - k > z\) holds, then

  1. if \(k > z\), we have that \(k + 1 > z + 1 > z\), or
  2. otherwise \(2z + 1 - k > z\), which means that \(2z + 1 - (k + 1) = 2z - k \ge z\), and therefore either

in each case for which \(P(k + 1)\) is true.